Kultūrinių archetipų recepcija planuojant urbanistinę renovaciją - Petrušonis, Vytautas (Journal of Architecture and Urbanism, 2011)
Reception of cultural archetypes in the planning of urban renovationIn the planning of urban renovation, interests, intentions and potentials of a large variety of actors of an urban environment must be taken into account. In urban regulations, statements should be formulated on the groundwork of collective psychology rather than on the basis of categories of individual psychology. This can strengthen consensual basis, which is important for effective communication to all actual actors of urban renovation. In this aspect, the role of cultural archetypes is especially important. Thanks to the cultural archetypes, the cultural context – that can encourage more adequate and reasonable comprehension of the meaning of urban environment elements in a renovation process – can be better actualized. The article provides the analysis on the extent the cultural archetypes are reflected in statements of documents fulfilling the regulative function. The critical analysis and evaluation of the conceptual basis of the urban renewal process allow concluding that the reception of cultural archetypes essentially does not occur for the reason of domination of descriptive narratives, which emerge from mythological narratives for the purpose of a creative process required to present and disclose the pre-logic existential experience, which is usually very important. Therefore, chances to achieve consensus with the society on urban renovation based on such regulations are very thin. Alternative approaches for statement formulation to be used in regulative documents are also introduced in the presented article.Article in Lithuanian.Santrauka. Planuojant urbanistinę renovaciją turi būti atsižvelgta į daugybės subjektų, darančių įtaką miesto aplinkos tvarkymui, interesus, intencijas ir galimybes. Konsensinį pagrindą gali sustiprinti projektavimo eigą veikiančių „teiginių“ formulavimas neapsiribojant individo psichologijos kategorijomis, o tokių informacinių vienetų formavimo procese didesnį dėmesį skiriant kolektyvinės psichologijos plotmei. Būtent tai gali atlikti kultūriniai archetipai, kurie praplečia kultūrinį kontekstą ir paskatina adekvatesnį bei motyvuotesnį renovuojamos urbanistinės aplinkos elementų reikšmės suvokimą. Nagrinėjama, kokiu laipsniu urbanistinę renovaciją veikiančiuose reglamentiniuose teiginiuose atspindima su kultūriniais archetipais susijusi plotmė. Kritiškai išanalizavus ir įvertinus urbanistinės renovacijos proceso idėjinius pagrindus, nustatyta, kad kultūrinių archetipų recepcija iš esmės nepasireiškia, nes dominuoja deskriptyvieji naratyvai, užgožiantys mitologinius naratyvus, labai svarbius egzistencinei ikirefleksinei patirčiai prezentuoti kūrybiniame procese. Aptariami alternatyviniai renovacijos planavimo reglamentavimo būdai.Reikšminiai žodžiai: urbanistinė renovacija, kultūros paveldo apsauga, kultūriniai archetipai, deskriptyvusis naratyvas, mitologinis naratyvas, užstatymo morfotipas.First Publish Online: 22 May 2013